Mostra della Fotografia Italiana 1953. Ambizioni disattese del progetto di Giuseppe Cavalli - Santoro, Lorena (Rivista di studi di fotografia. Journal of Studies in Photography, 2020)
This essay proposes a reconstruction of the critical reception of the Mostra della Fotografia Italiana 1953 curated by Giuseppe Cavalli. Through the analysis of the main specialized periodicals, the article highlights the scarce incisiveness of the exhibition on the national photographic scenary, showing it, at the same time, as an event that appears obsolete and that represents the beginning of Cavalli’s decline in Italy.